2009
DOI: 10.1063/1.3156805
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of the H2+CO+ reaction on an interpolated potential energy surface

Abstract: A potential energy surface that describes the title reaction has been constructed by interpolation of ab initio data. Classical trajectory studies on this surface show that the total reaction rate is close to that predicted by a Langevin model, although the mechanism is more complicated than simple ion-molecule capture. Only the HCO(+) + H product is observed classically. An estimate of the magnitude of rotational inelastic scattering is also reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…As shown in Figure 12, the average final angular momentum reduces with increasing impact parameter. This trend is in good agreement with the reported results by Ramazani et al 63 for inelastic collision investigation.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
“…As shown in Figure 12, the average final angular momentum reduces with increasing impact parameter. This trend is in good agreement with the reported results by Ramazani et al 63 for inelastic collision investigation.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
“…To study the dynamics of a reaction, a large number of molecular configurations in PES is also needed. Collins introduced a method (Growing program) to construct molecular PES with classical trajectory simulations . The Grow methodology was developed PES by a modified Shepard interpolation method.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the interaction of charged molecules with He is expected to be generally different from the one with H 2 (i.e. possible presence of reactive channels Ramazani et al 2009), and one could anticipate that at the opposite of what has been found for neutral species (Wernli et al 2006; Lique et al 2008; Dumouchel, Faure & Lique 2010; Dumouchel, Kłos & Lique 2011), rate coefficients of anions with He may not be an estimate of the one with H 2 .…”
Section: Introductionmentioning
confidence: 96%